Impact of Yoga on the Psychology of Secondary School Students - Rohtash (South Eastern European Journal of Public Health, 2025)
In the past few years, mental health issues among secondary school students have increased because of several factors such as academic pressure, social dynamics, and personal development challenges. Yoga is a mind-body practice that has been explored as an intervention to support students' psychological well-being, including physical postures, breathing exercises, and meditation. This research explores the effect of yoga on the psychological well-being of secondary school students, with a focus on anxiety, depression, self-esteem, and coping mechanisms. A structured yoga program over 08 weeks was administered and then compared at baseline and follow-up through standardized psychological assessments. The findings suggest that yoga seriously reduced anxiety, improved self-esteem, and enhanced coping strategies in maintaining better emotional regulation and mental resilience within the secondary school students. Through this paper, it can be argued that the inclusion of yoga to the school curriculums may be the gateway to a vital tool in promoting mental health across adolescents.